Intra-aural tick infestation, the presentation and complications - N, Srinovianti; Raja Lope Ahmad, Raja Ahmad Al'konee (The Faculty of Medicine, International Islamic University Malaysia, 2003)
Background : Tick in the ear is very painful and distressing. It grips firmly into the skin of the external auditory canal and the tympanic membrane. Ear examination and attempt to remove the tick from the ear is difficult especially in a frightened and irritable child. We aim to specify the safest way to handle patient with intra-aural tick.